AFFORDABILITY AND EFFECTIVENESS OF SOLAR PHOTOVOLTAIC SYSTEM’S AS A PANACEA FOR CLIMATE CHANGE MITIGATION AND SUSTAINABLE DEVELOPMENT IN KANO METROPOLIS - Luka, Fitto Buba; Abubakar, Aminu Yusuf; Mohammed, Mansur Abdul (FUDMA JOURNAL OF SCIENCES, 2023)
The study assessed affordability and effectiveness of solar photovoltaic (PV) energy technologies for electricity generation in Kano Metropolis. Three local government areas were selected purposively namely Tarauni, Nassarawa and Ungogo. Household and Small-Scale Business users of solar PV energy and technicians were selected using snowball sampling, while marketers of the PV facilities were selected purposively. Data was analysed using SPSS software version 23 by IBM. The findings revealed that most of the users of solar PV systems considered the prices that was mostly within the range of $487-$973 for households and $292-$487 for small-scale businesses as affordable. Almost all users adjudged their systems as being efficient, durable and enhanced their profit in the investments. A significant number of users, technicians and sellers of the facilities were optimistic that there is widespread use of PV system consequently reduce the use of generator sets and therefore the greenhouse gases emitted by generator will also be reduce. However, high initial investment cost, improper installation, lack of awareness, sub-standard products, lack of government support were the major factors militating against the utilization of the solar PV energy around Kano Metropolis. Governments, International NGOs and Banks should provide low interest loans and grants to solar products producers, importers and users in the country. Subsidy and tax incentives to solar equipment producers, importers and users should be provided.
Keywords: Electricity; energy; greenhouse gases; photo voltaic; clean energy